Legal prerequisites for the exemption from the inheritance and gift tax on the acquisition of agricultural land - Ofiarski, Zbigniew (Przegląd Prawa Rolnego, 2024)
The aim of the article is to assess the premises justifying the exemption from inheritance and gift tax upon the acquisition of agricultural land. The hypothesis about the legislator's extra-fiscal motives determining the legal construction of the tax exemption has been positively verified as it should be so framed as to encourage taxpayers to maintain the current use of the acquired agricultural land. In particular, the subject of the analysis included issues related to the prerequisites for the application of this exemption. It has been shown that only land subject to the exemption is land acquired and forming part of an agricultural holding within the meaning of the tax legislation. The essence of the area limits included in the legal construction of the tax exemption promoting the creation of family farms has been interpreted, and reference has been made to the required period during which an agricultural holding should be run to constitute a condition for applying for the exemption and determining its amount as determined by the thresholds of de minimis aid in agriculture. In conclusion, the author states, inter alia, that only the cumulative fulfilment of all the conditions entitles the purchaser of agricultural land to the tax exemption.